Understanding carbon sequestration, allocation, and ecosystem storage in a grassed vineyard - Callesen Torben, Oliver (2023)
Understanding if and to which extent a crop can act as a carbon sink is the basis of the assessment of its sustainability in the climate change context. Grassed vineyards have been indicated in the recent past as potentially large carbon sinks, questioning the assumption that crops are in general carbon sources. To this end, we conducted a detailed study along a growing season in a grassed mountain vineyard with two varieties (Chardonnay and Sauvignon blanc) to quantify the overall carbon stock of the system and to attribute the carbon fluxes to the specific components of the carbon cycle of the agroecosystem, including vines organs (shoots, fruits, roots), grasses (shoots and roots) and soil. We combined eddy covariance, soil respiration, biometric measurements, and soil analysis. Our findings determined the studied vineyard to be a moderate carbon sink. We found a gross primary production (2409 ± 35 g C m-2) much larger than previous data for vineyards, but the NEP (246 ± 54 g C m-2) of the growing season was on the lower end of previous reports. Based on similar above-ground net primary production values for the grapevines and herbaceous vegetation, we confirmed that the grassed alleys play an important role in overall carbon accumulation. We also observed that the soil represents by far the largest carbon storage, being the carbon retained by vegetation at harvest time only 7.3% of the total. The overall carbon stored in the vineyard (152.1 ± 7.1 t C ha-1) was less than that of forests and some orchards primarily due to the lower amount of plant biomass. Permanent grassland sites generally contained much higher amounts of carbon in the topsoil, indicating that there are vineyard characteristics or management practices which limit long term storage in this pool. Further studies are needed to unravel the relative contribution of the grapevines and grasses to overall gross primary productivity and carbon storage potential, especially in the context of different management decisions and the increasing frequency of drought events in similar mountain environments.